Immediate administration of antiviral therapy after transplantation of hepatitis C‐infected livers into uninfected recipients: Implications for therapeutic planning. Issue 6 (3rd February 2020) - Bethea, Emily; Arvind, Ashwini; Gustafson, Jenna; Andersson, Karin; Pratt, Daniel; Bhan, Irun; Thiim, Michael; Corey, Kathleen; Bloom, Patricia; Markmann, Jim; Yeh, Heidi; Elias, Nahel; et al.
Abstract : The practice of transplanting hepatitis C (HCV)‐infected livers into HCV‐uninfected recipients has not previously been recommended in transplant guidelines, in part because of concerns over uncontrolled HCV infection of the allograft. Direct‐acting antivirals (DAAs) provide an opportunity to treat donor‐derived HCV‐infection and should be administered early in the posttransplant period. However, evidence on the safety and efficacy of an immediate DAA treatment approach, including how to manage logistical barriers surrounding timely DAA procurement, are required prior to broader use of HCV‐positive donor organs. We report the results of a trial in which 14 HCV‐negative patients underwent successful liver transplantation from HCV‐positive donors. Nine patients received viremic (nucleic acid testing [NAT]‐positive) livers and started a 12‐week course of oral glecaprevir‐pibrentasvir within 5 days of transplant. Five patients received livers from HCV antibody‐positive nonviremic donors and were followed using a reactive approach. Survival in NAT‐positive recipients is 100% at a median follow‐up of 46 weeks. An immediate treatment approach for HCV NAT‐positive liver transplantation into uninfected recipients is safe and efficacious. Securing payer approval for DAAs early in the posttransplant course could enable need‐based allocation of HCV‐positive donor organs irrespective of candidate HCV status, while averting chronic HCV allograft infection. Abstract : Immediate administration of direct‐acting antiviral therapy to hepatitis C–negative recipients transplanted with livers from hepatitis C–positive donors is safe and results in rapid and permanent viral clearance and favorable clinical outcomes.